2021
DOI: 10.1111/jonm.13384
|View full text |Cite
|
Sign up to set email alerts
|

Job engagement and satisfaction are associated with nurse caring behaviours: A cross‐sectional study

Abstract: Caring behaviours are central to nursing practice. It is the act of caring that identifies the uniqueness of the profession and its distinct character from the other. Compelling evidence suggests that nurse caring behaviours are related to increased patient recovery (Lindberg et al., 2016;Yau et al., 2019), high patient satisfaction (Abdullah et al., 2017;Calong Calong & Soriano, 2018), improved quality of care and reduced occurrences of missed nursing care (Labrague, De los Santos, et al., 2020). Conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 54 publications
5
8
0
Order By: Relevance
“…Furthermore, nurses and midwives who reported higher levels of personal satisfaction with their nursing and midwifery work were six times more likely than those who reported lower levels of personal satisfaction to demonstrate higher levels of caring behavior. This finding was supported by other studies conducted in Carolina [ 38 ], Philippines [ 39 ], Indonesia [ 40 ], South Africa [ 41 ], and Ethiopia [ 14 , 16 , 17 , 24 ]. Caring may be a personal and professional value, as well as a nursing/midwifery identity, which may influence perceptions of caring behaviors [ 16 ].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, nurses and midwives who reported higher levels of personal satisfaction with their nursing and midwifery work were six times more likely than those who reported lower levels of personal satisfaction to demonstrate higher levels of caring behavior. This finding was supported by other studies conducted in Carolina [ 38 ], Philippines [ 39 ], Indonesia [ 40 ], South Africa [ 41 ], and Ethiopia [ 14 , 16 , 17 , 24 ]. Caring may be a personal and professional value, as well as a nursing/midwifery identity, which may influence perceptions of caring behaviors [ 16 ].…”
Section: Discussionsupporting
confidence: 84%
“…4 Research has continued to explore and demonstrate the impact of nurses' work engagement on work outcomes. [5][6][7][8][9] Understanding the factors that predict and drive work engagement has been essential in developing meaningful interventions and programs. Previous studies have identified some predictors of work engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Nurse caring behaviour is beneficial not only to the patient but also to nurses themselves. Nurse caring behaviour is significantly correlated with job engagement (De Los Santos & Labrague, 2021 ), job satisfaction (De Los Santos & Labrague, 2021 ; Putra et al, 2021 ), and professional quality of life (Inocian et al, 2021 ). As a result, nurse caring behaviour is more important than ever during the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%